Perfect phrases for office professionals : hundreds of ready-to-use phrases for getting respect, recognition, and results in today's workplace - 274784 Runion, Meryl; Fenner, Susan W. 520077 (New York : McGraw-Hill)
Mohd Ashraf Mohd Sobli;